Guiding principles for quality, ethical standards and ongoing learning in implementation research: multicountry learnings from participatory action research to strengthen health systems. (6th November 2020) - Ozano, Kim; Dean, Laura; Adekeye, Oluwatosin; Bettee, Anthony K; Dixon, Ruth; Gideon, Ntuen Uduak; Gwani, Noela; Isiyaku, Sunday; Kollie, Karsor; Lar, Luret; Oluwole, Akinola; Piotrowski, Helen; et al.
Abstract: Global health gains can be achieved through strengthening health systems to identify and address implementation challenges in low- and middle-income countries. Participatory research, that promotes joint problem and solution finding between communities and different health systems actors, supports policy implementation analysis at all levels. Within the neglected tropical disease programmes in Liberia and Nigeria, we applied participatory action research (PAR) to address programmatic and health system bottlenecks with health systems strengthening embedded. This paper shares learning from 20 interviews with co-researchers, from national and sub-national levels and academic researchers who worked collaboratively to understand challenges, co-create solutions and advocate for policy change. Through analysis and reflections of existing PAR principles, we inductively identified five additional guiding principles for quality, ethical standards and ongoing learning within PAR projects that aim to strengthen health systems. (1) Recognize communities as units of identity and define stakeholder participation to ensure equitable engagement of all actors; (2) enable flexible action planning that builds on existing structures whilst providing opportunities for embedding change; (3) address health systems and research power differentials that can impede co-production of knowledge and solution development; (4) embed relational practices that lead to new political forms of participation and inquiry within health systems and (5) develop structures for ongoing learning at multiple levels of the health system. PAR can strengthen health systems by connecting and co-creating potentially sustainable solutions to implementation challenges. Additional research to explore how these five additional principles can support the attainment of quality and ethical standards within implementation research using a PAR framework for health systems strengthening is needed.